Islam or progress of the nation?: an assessment of the aurat issue in Malay newspapers and magazines in the 1930s - Nazirah Lee; Zanariah Noor (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
Western media often perceive Islam as a misogynistic religion which hampers the progress of a nation. One related issue is “aurat” which is considered as a means to denigrate women in the society. In pre-Independent Malaya debates raged around the contested perceptions and interpretations of aurat in its relation to Malay modernisation and the urgency of achieving ‘progress’ for Malays on par with other communities in the country. Articles were published in Malayan newspapers and magazines debating the need to enhance awareness about the progress of the Malay nation. This study assessed the differing interpretations of the principle of aurat among Muslims in 1930s Malaya. The information scrutinised was derived from polemics published in Malay newspapers and magazines circulated in Malaya in the 1930s. The findings revealed that people were torn between modernization and traditionalism, viewing them as a choice between westernization and Islam. The establishment of secular education and social mixing with the non-Muslim community exposed the Malays to new norms and values. In this transitional period, social norms and values transformed according to the surroundings. The materials demonstrated how the Malay Muslims responded to the call of development and the extent to which they were ready to embrace modernization, which some viewed as a detachment from prestine Islamic teachings, especially regarding the issue of aurat.